STRUKTUR DAN KULTUR DOMINASI: RELASI AGENSI DAN STRUKTUR DALAM PEMBENTUKAN KULTUR PRAJURIT TNI ANGKATAN DARAT PADA ERA REFORMASI - , Kitaran Joy Sihontang ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Institutionally, the Indonesian National Military (TNI) in the New Order era dominated the social and political system in Indonesia. The domination ended by the falling of the Soeharto regime and the emergence of the Reformation era. Some regulations indicating the ending of the domination include the Decree number 3 issued in 2002 on National Defense, the Decree number 34 on TNI, a decree issued by the Indonesian Legislative Body (TAP MPR) No. VI in 2000 on the separation of the Indonesian National Police (POLRI) from the TNI and the TAP MPR No.VII in 2000 on the roles of TNI and POLRI. In addition, the TNI has institutionally gone through some reformations and reorganizations including reposition, redefinition and institutional reformation. Nevertheless, the TNI has not undertaken cultural reformation especially on the military-cultural personnel although institutionally it has done so. On the military-cultural personnel aspect, the TNI personnel culture is still dominated by the long-existing feudalistic. This work, therefore, focuses on the practices of militancy, discipline, loyalty, and esprit de corps as the four basics of the culture of the TNI personnel. To discuss the issue, this project employs the agency and structure of Anthony Giddens and habitus of Pierre Bourdieu theories for analytical purposes. The data collection of this qualitative work is conducted through observation, in-depth interview and focused group discussion (FGD) with a number of key informants from the TNI AngkatanDarat (Indonesian army), from those with lower, middle and upper ranks as well as those who are pension from the TNI AD with experience of having strategic positions. Documentation is also done to support the data collection for important documents and library research to support literature data. The data is analyzed in a qualitative way using categories with interpretive and descriptive approaches. The work finds that militancy, discipline, loyalty, and esprit de corps of the TNI AD personnel is originated from conscious interaction between personnel as the agent and the TNI AD as the structure having a rule and punishment system. The interaction is mutual contributive and interinfluencing. The influence is internal and contextual leading to establish a doxa. This culture of personnel becoming the doxa grows effectively in the military training and education process. Thus, the era of training and education of personnel plays as the field or the place of the growing of the culture of the TNI AD personnel. Besides the interaction that is internally inter-influencing, this project also finds that the internal interaction is also influenced externally from the feudalistic culture inherited from the Javanese kingdoms in the past. The combination of the internal and external aspects in the formulation of the culture of the TNI AD personnel lead to the growing of the culture of domination in the institution, which is hard to reform since it is internalized by the personnel in a perceptional and long period of time. Finally, this work recommends that the materials and contents of the training and education need to be reformed so that they are anthropologically and culturally supporting the better culture building. The TNI AD is encouraged to enrich the perspectives of the materials for the training and education, especially from Indonesian cultures but not the feudalistic one. The cultural changes are to lead to the use of humanistic approach in the formulation process of the culture of the TNI AD personnel.